Fermi Arcs Dominating the Electronic Surface Properties of Trigonal PtBi 2 - Hoffmann, Sven (2024)
Materials combining topologically non-trivial behavior and superconductivityoffer a potential route for quantum computation. However, the set of availablematerials intrinsically realizing these properties are scarce. Recently, surfacesuperconductivity has been reported in PtBi2 in its trigonal phase and aninherent Weyl semimetal phase has been predicted. Here, based on scanningtunneling microscopy experiments, the signature of topological Fermi arcs arerevealed in the normal state patterns of the quasiparticle interference. It isshown that the scattering between Fermi arcs dominates the interferencespectra, providing conclusive evidence for the relevance of Weyl fermiology forthe surface electronic properties of trigonal PtBi2.